Microbiological Evaluation of Retail Veal Meat in the City of Al Bayda, libya - Randa Mahmoud; Mahmoud Gaballa; Ibrahim Alsadi; Abdulsalam Saleh; Mohammd Abd Alati; Alaa Alrahman Abid (AlQalam Journal of Medical and Applied Sciences, 2024)
By examining veal carcasses sold in Al Bayda and surrounding areas this study assessed the microbiological status in 2020. Eighty pieces of veal one for each of the shoulder, head, ribs, and thigh regions were randomly selected from several places selling the meat. Locations Aerobic plate count (APC) and enterobateriaceae were measured. In addition to isolating and identifying Salmonella and E. coli bacteria the presence of which indicates contamination they were found in samples taken from meat markets. The results showed the presence of APC in all different cuts of veal samples that were examined and evaluated during the study. We found the highest number of APC in thigh samples (1.3×106) and the lowest number found in rib meat samples (9.5×105). Regarding food poisoning bacteria six (30%) seven (35%) six (30%) and four (20%) of the twenty subjects had positive tests for Salmonella in the shoulder, ribs, and thighs. However, of the veal samples tested 18 (90%) 16 (80%) 15 (75%) and 19 (95%) contained E. coli. The results showed that a wide range of microorganisms from different sources may be present in fresh cuts of veal. This highlights the need to follow strict health precautions when handling cooking and slaughtering animals. It also highlights the need for regulatory authorities to take all necessary measures especially in light of the absence of inspection, sealing and cleanliness procedures for carcasses. في هذه الدراسة تم فحص ذبائح العجول المُباعة في مدينة البيضاء والمناطق المحيطة بها وكان ذلك في عام 2020. تم اختيار ثمانين قطعة من لحم العجل لكلا من مناطق الكتف والرأس والضلوع والفخذ بشكل عشوائي من عدة أماكن لبيع اللحوم. تم قياس أطباق العد الهوائية والبكتيريا المعوية. بالإضافة إلى عزل وتحديد بكتيريا السالمونيلا والإشريكية القولونية التي يُشير وجودها إلى تلوث تم العثور عليه في عينات مأخوذة من أسواق اللحوم. أظهرت النتائج وجود عدد أطباق العد الهوائية في جميع القطع المختلفة لعينات لحم العجل التي تم فحصها وتقييمها أثناء الدراسة. وجدنا أكبر عدد من أطباق العد الهوائية في عينات الفخذ (1.3 × 106) وأقل عدد موجود في عينات لحوم الأضلاع (9.5 × 105). فيما يتعلق ببكتيريا التسمم الغذائي، كان لدينا ستة (30٪) سبعة (35٪) ستة (30٪) وأربعة (20٪) من العينات العشرين اختبارات إيجابية للسالمونيلا في الكتف والضلوع والفخذين. ومع ذلك، من بين عينات لحم العجل اختبرت 18 (90٪) 16 (80٪) 15 (75٪) و19 (95٪) تحتوي على الإشريكية القولونية. أظهرت النتائج أن مجموعة واسعة من الكائنات الحية الدقيقة من مصادر مختلفة قد تكون موجودة في قطع جديدة من لحم العجل. يُسلط هذا الضوء على الحاجة إلى اتباع الاحتياطات الصحية الصارمة عند التعامل مع الطهي وذبح الحيوانات. كما نرى ضرورة أن تتخذ السلطات الرقابية جميع التدابير اللازمة خاصة في ظل عدم وجود إجراءات تفتيش وختم ونظافة الذبائح.